ASEAN Students' Interest in Learning the Indonesian Language: A Descriptive Study from the Perspective of SEAMEO ASEAN - Hardini, Tri Indri; Yulianeta, Yulianeta; Fikrianto, Misbah; Hamidah, Hasanatul; Emilia, Emi; Kharismawati, Limala Ratni Sri (International Journal of Language Education, 2023)
Language plays a crucial role in the educational environment, whether in schools or universities. Besides the national language, students are also exposed to regional and foreign languages to enhance their language proficiency. Teaching foreign languages encompasses a wide range of options, such as English, Korean, Japanese, and Chinese. Moreover, languages affiliated with ASEAN countries, like Malay, Thai, and Indonesian, have gained popularity. This study employs a descriptive approach to elucidate the findings regarding the interest in learning Indonesian among students in ASEAN nations. Conducted by SEAMEO ASEAN, the research draws its primary data from questionnaires and presentations submitted in September 2022. Participating ASEAN countries in this SEAMEO initiative encompass Brunei Darussalam, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor Leste, and Vietnam and analyzed with descriptive statistical analysis. The study reveals a notable demand for Indonesian language learning among students from ASEAN countries. Indonesian is pursued for various purposes, including professional, socio-cultural, and personal development. Recognizing the interest in Indonesian among ASEAN students provides a foundation for the implementation of Indonesian as a foreign language through the BIPA program. There has not been much research on the interest of Indonesian language among students at the ASEAN level, therefore this research is included in the initial research on Indonesian language internationalization policies starting from the ASEAN level